Evaluation of External Genital Anomalies and the Underlying Factors in Male Newborns - Abdolghader Pakniyat; Mohammad Reza Fallah; Zahra Fakour; Farzad Moloudi; Seyran Khezri; Sima Masoudi (Mashhad University of Medical Sciences, 2016)
Background: External genital anomalies are the most common congenital disorders in male infants with unknown etiology in the majority of cases. According to recent reports, incidence rate of these anomalies is rising in different countries. This study aimed to evaluate the prevalence of external genital anomalies and possible underlying factors in male newborns. Methods: This cross-sectional study was conducted on all the male neonates born in Motahari Hospital of Urmia during October 2009-June 2010. Neonatal screening results and demographic data were recorded separately in a questionnaire for each neonate. Data analysis was performed in SPSS V.20 using descriptive statistics (mean, frequency, percentage, and standard deviation) and Chi-square test to evaluate the correlations between quantitative variables. Results: In this study, external genital anomalies were identified in 83 male neonates (8.3%). Moreover, 59 infants (5.9%) had cryptorchidism, 18 (1.8%) had hypospadias and 12 infants (1.2%) had microphallus. Moreover, a significant correlation was observed between the incidence of cryptorchidism and maternal comorbidities, low birth weight, prematurity, maternal gestational hypertension, and diabetes mellitus. Conclusion: According to the results of this study, cryptorchidism is the most prevalent external genital anomaly in male newborns, followed by hypospadias. Occurrence of these anomalies is associated with several risk factors, such as prematurity, low birth weight, maternal diseases (e.g., diabetes and hypertension), and use of medications during pregnancy. In addition, cryptorchidism had a significant correlation with smoking habits, and further studies with larger sample sizes are required in this regard.